The intention of green products purchasing among Malaysian consumers: a case study of Batu Pahat, Johor - Lee, Te Chuan; Mokan, Kogila Vani; Bhoyar, M. R. (Institute of Medico-Legal Publications, 2018)
Green product known as environmental friendly product which harmless to the earth and the product that can be recyclable from non-toxic resources.The problems that encourage conduct this research are environmental problem, lack of literature research about the green products purchasing intention and minor companies involved in green production in Malaysia.In order to address this issue, this study aimsto investigate the intention of Malaysian consumer towards purchasing the green product and to identify the relationship between knowledge, eco-label and social influences towards consumer purchase intention. Quantitative method was used to collect data through structured survey questionnaire from 200 shoppers at three selected shopping malls in Batu Pahat, Johor. However, from the 200 questionnaires only 93 were acceptable. The data collected were analysed using Statistical Package for the Social Science (SPSS) version 24.0. The findings revealed that the level of mean analysis indicated all items were positively influences consumer purchase intention. Besides, the spearmen correlation coefficient test showed that knowledge, eco-label and social influences were positively significant with consumer purchase intention.